Occupy the earth global environmental movements - Kedzior, Sya Buryn; Leonard, Liam (Advances in sustainability and environmental justice ;, 2014)
The onset of global concerns about environmental risks, climate change and threats to the planet from industry have focused the minds of a generation. Throughout the world, new movements are emerging in an attempt to challenge those who would put profits before the planet. This volume brings together global contributions that represent the cutting edge of research in the area of global environmental movements. Contributions include chapters on the spatial impacts of environmental groups in Israel, the work of Greenpeace in Brazil, environmental activism in Ireland, animal rights and anti-hunt activism in Malta, the global de-growth movement, environmental movement mobilization in China, and anti-pollution activism in India. The scope and breath of this research indicates the emergence of both a global grassroots environmental mobilization in addition to analysis and documentation of these responses by researchers world-wide. With increased threats from climatic change and ecological degradation being highlighted as a threat to much of the world's population in the coming century, this activism and ensuing research becomes all the more significant.